Analysis of reasons for dissemination of destructive forms of acute apendicitis in children - V.S. Konoplitskyi; V.V. Pogorilyi; U.A. Dymchina; T.I. Michalchyk; U.Ye. Korobko (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2020)
The aim of the study to determine the main causes of destructive forms of acute appendicitis (AA) based on the analysis of quantitative characteristics of the pathology in children of Vinnytsia region in the period from 2005 to 2018. Materials and methods. To implement the study, a retrospective analysis of 980 medical records of patients treated at the Vinnytsia Regional Clinical Hospital with destructive forms of AA in the period 2005-2018. The age of children was from 1.5 to 18 years. Results. The results of research show that the destructive forms of appendicitis more frequently affect the boys, especially the junior school age. The reason for the late detection of AA is self-medication and errors in diagnosis. Most patients refered to medical help for the first 2 days after beginning of abdominal pain. In the structure of complications predominated: local peritonitis, omenitis and typhlitis. Conclusions. It is necessary to pay attention to the availability of medical care to the population, especially in rural areas, to hold sanitary and educational work, and more widely use instrumental methods such as ultrasound diagnostic and computed topography of the abdominal cavity. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of participating institution. The informed consent of the patient was obtained for conducting the studies.